2009
DOI: 10.1128/jcm.00240-09
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing Analysis of 20 Nucleotides of Internal Transcribed Spacer 2 Discriminates Candida parapsilosis , Candida metapsilosis , and Candida orthopsilosis

Abstract: Two new cryptic sister species, Candida orthopsilosis and Candida metapsilosis, were recently identified by consistent DNA sequence differences among several genes within the genetically heterogeneous Candida parapsilosis complex. Here, we present data demonstrating that Pyrosequencing analysis of 20 nucleotides of internal transcribed spacer region 2 rapidly and robustly distinguishes between these three closely related Candida species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…We have previously demonstrated that pyrosequencing of 35 bp of a portion of the internal transcribed spacer region 2 (ITS2) is sufficient to robustly identify the vast majority of pathogenic yeasts (27), including genetically closely related isolates within species complexes (28,29). This is also the case for the key species within the C. albicans species complex.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…We have previously demonstrated that pyrosequencing of 35 bp of a portion of the internal transcribed spacer region 2 (ITS2) is sufficient to robustly identify the vast majority of pathogenic yeasts (27), including genetically closely related isolates within species complexes (28,29). This is also the case for the key species within the C. albicans species complex.…”
Section: Resultsmentioning
confidence: 93%
“…All 1,839 test isolates were subjected to pyrosequencing analysis of a portion of ITS2 exactly as described previously (27)(28)(29). For isolates identified by pyrosequencing as C. africana, identity was confirmed by PCR amplification and sequencing of a region of the large subunit gene (LSU) and the internal transcribed spacer 1 (ITS1) region using the primers described previously (30,31) and direct inoculation of PCR products with yeast suspensions as described in reference 32.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of strain typing methods have been used for the differentiation of the C. parapsilosis family, including electrophoretic karyotype (EK) analysis (9,35), DNA fingerprinting with probe Cp3-13 (11), RAPD analysis (10,42), RFLP analysis (38,39), multilocus sequence typing (MLST) (36), and pyrosequencing (2). van Asbeck et al (38) compared three of these molecular typing methods, ITS sequencing, RAPD anal- ysis, and RFLP analysis, and indicated that ITS1 typing and RFLP analysis appear to have similar potentials to differentiate C. parapsilosis and both have discriminatory abilities superior to the discriminatory ability of RAPD analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular methods can be also applied for identification of isolates, e.g. pyrosequencing of target genes (Borman et al, 2009;. Further development of modified media and combinations of temperature, pH, aerobic/anaerobic conditions and moisture would probably increase the number of isolated yeasts, it is however laborious and very time consuming.…”
Section: Methods For Investigating Biodiversity Of the Yeasts From Gitmentioning
confidence: 99%